Evaluating Economic Feasibility and Environmental Benefits of Solar Cell Systems in the Mining Industry: A Case Study of the Gunung Mergi Quarry Mining Office - Praditya Yuda Adji Perkasa; Silviana Silviana; Singgih Saptadi; Marcelinus Christwardana (Journal of Bioresources and Environmental Sciences, 2025)
The annual electricity consumption at the Gunung Mergi Mining Office, which reaches ±55,000 kWh, incurs significant operational costs, necessitating a more efficient and sustainable energy supply alternative. To address this need, a technical simulation was conducted using Helioscope software to determine the appropriate rooftop solar power system configuration based on the roof conditions and solar radiation potential at the location. An economic analysis was performed using the Payback Period, Net Present Value (NPV), and Profitability Index (PI) methods to assess the feasibility of the investment. The simulation results show that a roof area of 474.41 m² can accommodate 54 solar modules with a capacity of 550 Wp, with an energy production of ap-proximately ±46,000 kWh per year or capable of meeting 84-85% of the office's electricity needs, and has the potential to save IDR 40-46 million per year. The financial analysis resulted in a positive NPV of IDR 20,076,884, an IRR of 1.078, and a Discounted Payback Period of 22.1 years, which is still within the technical lifespan of solar panels. From an environmental perspective, supplying most of the office’s electricity from rooftop solar can substantially reduce Scope 2 emissions associated with PLN electricity use, thereby lowering the carbon footprint of non-productive mining facilities. These findings indicate that the implementation of rooftop solar power plants is feasible and supports cost efficiency and the transition to clean energy in the mining sector.